On Reconstructing Proto-Bantu Grammar - Bostoen, Koen de Schryver, Gilles-Maurice Guérois, Rozenn Pacchiarotti, Sara; Pacchiarotti, Sara; Guérois, Rozenn; de Schryver, Gilles-Maurice (My University, 2022)
This book is about reconstructing the grammar of Proto-Bantu, the ancestral language at the origin of current-day Bantu languages. While Bantu is a low-level branch of Niger-Congo, the world’s biggest phylum, it is still Africa’s biggest language family. This edited volume attempts to retrieve the phonology, morphology and syntax used by the earliest Bantu speakers to communicate with each other, discusses methods to do so, and looks at issues raised by these academic endeavours. It is a collective effort involving a fine mix of junior and senior scholars representing several generations of expert historical-comparative Bantu research. It is the first systematic approach to Proto-Bantu grammar since Meeussen’s Bantu Grammatical Reconstructions (1967). Based on new bodies of evidence from the last five decades, most notably from northwestern Bantu languages, this book considerably transforms our understanding of Proto-Bantu grammar and offers new methodological approaches to Bantu grammatical reconstruction.
Keywords: Grammar; Proto-Bantu; Reconstruction